Aprendizagem do relevo terrestre por parte de educandos com deficiência visual - Pereira, Tassia Farencena (2017)
In a current Brazilian context, the inclusive education is an important resource in order to obtain a truly and fairly democratic society, for that reason extends to all citizens independent of their specificities and the access to knowledge resulting in the development of autonomy in these people facing the world. Logically, the discernment managed has to be considered and planned so as to satisfy the needs of what each educator presents. In this respect, thinking about the Geography thinking-learning process, this research intends to understand the perception and cognition process of aspects concerning land relief of two visually impaired persons, one is congenital and the other is acquired. Thus, this article aims at identifying the differences and similiarities presented by the two persons during the process in which the landscape was introduced in two models, and also through interviews before and after the contact with the educational resources. The experience of the educator researcher was also indicated regarding the obstacles faced during practice. Then, this article discusses terms such as perception, memory, learning, landscape, relief, and others in order to reflect the cognitive process in visually impaired people regarding spatial representation. It was verified that the spatial representation, as well as geographic concepts linked to it, is perceived more effectively by visual impaired students when the educator uses educational resources such as models to represent them. Therefore, it can be concluded that it is very important to work with concepts in a determined way so that students can recognize them, especially the congenitally blind student because the resource allows that a tangible memory about things the student was not visually aware can be established. As regards the student with acquired blindness, the visual memory is used often creating associations respecting things being studied. As a result, it can be noticed that every visually impaired person can apprehend concepts concerning spatial representation.